Investing in early childhood : its role in development - Sen, Amartya (IDB WashingtonUS, 1999)
Comments briefly both on a general approach to development that allows one to see the issue of investment in childhood in an inclusive perspective, and also on some of the distinct elements in the adult-childhood relationship that have to be more fully seized for an adequate policy approach to this complex issue.